THE INFLUENCE OF JOB SATISFACTION AND PSYCHOLOGICAL WELLBEING ON TURNOVER ON HOSPITAL EMPLOYEES - Amri, Abduh Rahmat; Ribhan; Ahadiat, Ayi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Health decentralization allows the Bandar Lampung City Health Office to designprograms and service activities that are appropriate to local conditions. Based on dataobtained from the HR department of private hospitals in Bandar Lampung City, thenumber of employees in private hospitals is 326 people and therate turnover reachesmore than 10% per year. The purpose of this study was to determine the relationshipbetween psychological well-being and job satisfaction with therate turnover at theBandar Lampung City Private Hospital. The results of the study found that JobSatisfaction and Psychological Wellbeing had a simultaneous effect on employeeturnover. This is evidenced by the statistical results of F count 18,539 > F table valueof 3.07, with a significance of 0.00; Job satisfaction has a significant effect on employeeturnover with a t-table value of 1.657 and a t-count value of 3.437; PsychologicalWellbeing has a significant effect on employee turnover, with t count of 6.051 whichmeans t count > t table (6.051> 1.657) and sig 0.00 < 0.05